(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Industrial design in the industry appear to be necessary for the artistic, aesthetic, and marketing promotion of products on the market. The demand for professionals with skills and critical evaluation of fact, is the policy priority of the educational system of industrial design.